HUBUNGAN POLA ASUH PERMISIF DENGAN KECANDUAN BERMAIN GADGET PADA ANAK PRASEKOLAH DI TK ISLAM CIPUTAT KOTA TANGERANG SELATAN - Susilawati; Gita Fitri Andini (STIKes IMC Bintaro, 2021)
Advances in technology are now very rapid and sophisticated, and almost all groups including children and toddlers are already using gadgets in the activities they do every day. Since using gadgets, when at home children become difficult to communicate, and less respond when parents ask to talk. Gadgets that are used excessively and out of control can have bad consequences. The role of parents at home is very important in the development of behavior and personality of children, parenting parents applied at home also varies. This study aims to determine the relationship between permissive parenting with addiction to playing gadgets in preschool children in Islamic Kindergarten Ciputat, South Tangerang. This type of research uses a quantitative approach with analytic survey research methods with cross sectional design. Sampling using the Lemeshow formula two different proportions test with a total sample of 82 samples. The research instrument used was a questionnaire sheet. The analysis technique used to determine the relationship using Chi-square of 82 respondents was found 52 respondents were not permissive parenting and 30 permissive parenting. With a P value of 0,000 <0.05 so it can be concluded Ha is accepted Ho is rejected, meaning that there is a relationship between permissive parenting with the addiction to playing gadgets in preschool children in Islamic Kindergarten Ciputat, South Tangerang.